2012
DOI: 10.1002/uog.11122
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation vs bipolar umbilical cord coagulation in the management of complicated monochorionic pregnancies

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
110
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 12 publications
15
110
4
2
Order By: Relevance
“…4 Reported methods for selective feticide include fetoscopic laser coagulation, bipolar cord coagulation, radiofrequency ablation, cord occlusion by ligation or photocoagulation and interstitial laser coagulation. [5][6][7][8][9][10] Perinatal survival rates following selective feticide vary between 65 and 92%, depending on indication and technique. 6 Reliable data on the long-term neurodevelopmental outcome in surviving twins is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…4 Reported methods for selective feticide include fetoscopic laser coagulation, bipolar cord coagulation, radiofrequency ablation, cord occlusion by ligation or photocoagulation and interstitial laser coagulation. [5][6][7][8][9][10] Perinatal survival rates following selective feticide vary between 65 and 92%, depending on indication and technique. 6 Reliable data on the long-term neurodevelopmental outcome in surviving twins is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Bebbington et al reported no neonatal or maternal adverse events with the use of RFA in 58 pregnancies 2 . In-utero limb ischemia has been a reported complication of TTTS 3 .…”
Section: Limb Arteriovenous Malformation Identified After Radiofrequementioning
confidence: 98%
“…Bipolar diathermy cord occlusion has been superseded by minimally invasive techniques, as the risks of pPROM and PTL were elevated (27%, 22%, respectively, survival 85%) [76]. Fetoscopic laser reports a 80% survival with pPROM in 18% and PTL in 3% within 28 days of procedure [79]; RFA reports a 70 -92% survival rate [76,80] with a pPROM and preterm labour rate of 14% and 7%, respectively [76]. Hence, minimally invasive techniques reduce but do not remove the risks, without changing survival rates.…”
Section: Twin-reversed Arterial Perfusion Sequencementioning
confidence: 99%